(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
The paper deals with the issue of the efforts undertaken by the bodies of party and state administration to fulfill plans and accelerated accumulation of reserves on the eve of the Great Patriotic War. The study is novel in that the analysis of attempts to work out a mobilization strategy for the socio-economic development of the USSR on the eve of the war was carried out based on a wide range of previously unpublished documents on file. The article delves into the loss of opportunities, and ignoration of several most appropriate value propositions to have proven their effectiveness but was introduced into practice only during the war years. The relevance of the research is due to the need to learn lessons from the historical experience of elaborating strategic plans for the country’s development, involving leading scientists in this work concerning scientifically grounded, objective data.